2017
DOI: 10.3346/jkms.2017.32.6.908
|View full text |Cite
|
Sign up to set email alerts
|

Increased Circulating T Lymphocytes Expressing HLA-DR in Kidney Transplant Recipients with Microcirculation Inflammation

Abstract: We consecutively enrolled 82 kidney transplant recipients (KTRs) with stable renal function and 24 KTRs who underwent indication biopsy to compare the histological grading of renal allografts with the activity of circulating T lymphocyte subsets and monocytes determined by flow cytometry, which were obtained at 2 weeks after kidney transplantation (KT) and at the time of indication biopsy, respectively. The sum of the scores of glomerulitis (g) + peritubular capillaritis (ptc), inflammation (i) + tubulitis (t)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…It was shown that HLA-DR expression on CD3 + T cells was higher in lupus patients with anti-DNA antibodies as compared to HC (47) and was higher on CD8 + T cells in patients experiencing a lupus flare (22). Similar observations were made in patients with rheumatoid arthritis (21, 53), antiphospholipid syndrome (54) and with rejection in solid organ transplantation (55).…”
Section: Discussionsupporting
confidence: 67%
“…It was shown that HLA-DR expression on CD3 + T cells was higher in lupus patients with anti-DNA antibodies as compared to HC (47) and was higher on CD8 + T cells in patients experiencing a lupus flare (22). Similar observations were made in patients with rheumatoid arthritis (21, 53), antiphospholipid syndrome (54) and with rejection in solid organ transplantation (55).…”
Section: Discussionsupporting
confidence: 67%
“…Among the histopathological findings, the MI sum score of the renal allograft was reported to be significantly associated with immune activation in peripheral blood. 27 Similarly, previous studies have demonstrated that the detection of de novo DSA was significantly associated with microvascular lesions or peritubular capillaritis scores, 28 but not with scarring lesions. 10 11 Contrary to previous evidences, in our experience, we could not find any pathologic correlation with de novo DSA.…”
Section: Discussionmentioning
confidence: 74%
“…To determine the contribution of circulating dnDSAs to graft injury, the correlation between DSAs in peripheral blood and histopathologic lesions in renal allografts was evaluated. MFI sum score of renal allografts was shown to be associated with immune activation in peripheral blood [25], and the presence of dnDSAs has been linked to microvascular lesions or peritubular capillaritis [26] but not to scarring lesions [27][28]. Contrary to previous evidence, we did not nd any pathologic correlations with dnDSAs; there was no signi cant association between MFI sum score and the number and MFI of DSAs, which could be explained by the fewer episodes of acute rejection in our study population.…”
Section: Discussionmentioning
confidence: 99%